Obstacles to inclusion and threats to civil rights: An integrative review of the social experiences of service dog partners in the United States - Sarah C. Leighton; Molly E. Hofer; Cara A. Miller; Matthias R. Mehl; Tammi D. Walker; Evan L. MacLean; Marguerite E. O’Haire (PLoS ONE, 2025)
Service dogs, trained to assist people with disabilities, are known to impact their human partners’ social experiences. While service dogs can act as a “social bridge,” facilitating greater social connection under certain circumstances, many service dog partners also encounter challenges in social settings because of the presence of their service dog – despite legal protections. Among the most common challenges reported are experiences of stigma, discrimination, and access or service denials. This preregistered integrative review sought to synthesize empirical, theoretical, and legal literature to understand better the social experiences reported by service dog partners in the United States, including (1) civil rights experiences; (2) experiences of stigma and discrimination; and (3) broader social experiences. Following database searches and article screening, a total of N = 43 articles met the eligibility criteria for inclusion. Analyses were conducted in two stages: first, synthesizing quantitative and qualitative findings to explore the magnitude of social experiences reported by empirical articles and second, narrative synthesis to integrate findings across all article types. Analyses identified three themes: Adverse Social Experiences, Contributing Factors, and Proposed Solutions. Overall, we found consistent reports of stigma, discrimination, and access denials for service dog handlers. Additionally, these adverse experiences may be more common for service dog partners with disabilities not externally visible (i.e., invisible disabilities such as diabetes or substantially limiting mental health conditions). This integrative review highlights a pattern of social marginalization and stigmatization for some service dog partners, exacerbated by inadequate legal protection and widespread service dog fraud. These findings have implications for the individual well-being of people with disabilities partnered with service dogs and highlight a need for collective efforts to increase inclusion and access. Effective solutions likely require a multi-component approach operating at various socio-ecological levels.